Docosahexaenoic Acid Supplementation in Postnatal Growth Restricted Rats Does Not Normalize Lung Function or PPARγ Activity - Adrienne J. Cohen; Wesley R. Chidester; Daniel T. Wray; Nicolette Jessen; Aimee Jones; Cheylah Bitsui; James Zhao; J. Alan Maschek; James E. Cox; Camilia R. Martin; Lisa A. Joss-Moore (Biomolecules)
The development of BPD in preterm neonates is increased by poor growth and nutritional deficits. The involvement of the fatty acid DHA in the development of BPD has been a focus for over a decade. However, recent clinical trials show that isolated DHA supplementation may increase BPD in subgroups of preterm neonates. One explanation for poor lung outcomes in DHA-supplemented neonates is a disruption of global fatty acid profiles and increased expression of a dominant-negative splice variant of a key driver of lung development, PPARγ. We previously developed a rat model of postnatal growth restriction (PGR) in which pups have impaired lung function and altered PPARγ activity. Here, we use our PGR rat model to assess the effects of DHA supplementation on lung outcomes. We hypothesize that the PPARγ splice variant, PPARγΔ5, will be expressed in the rat lung, and that DHA supplementation of PGR rat pups will alter circulating lipid profiles, lung mechanics, and PPARγ variant expression. Our findings demonstrate that PPARγΔ5 is expressed in the developing rat lung and that DHA supplementation of PGR rat pups alters global circulating fatty-acid profiles and does not normalize PGR-induced impaired lung mechanics or PPARγ activity.